Step-by-step explanation and answer:
The given equations P=2T=3Q can be split up into
P=2T..................(1)
P=3Q................(2)
since they are all equal.
Rewrite the given equation
3Q + 4T = 26 .............(3)
as
3Q + 2(2T) = 26 ...........(4)
and substitute (1) and (2) into (4)
P + 2(P) = 26 .................(5)
Multiply (5) by two to get
6P = 2*26 = 52 ..............(6)
as given.
Answer:
see explanation
Step-by-step explanation:
Given P = 2T = 3Q, then
3Q + 4T = 26 can be expressed as
P + 2P = 26
3P = 26 ( multiply both sides by 2 )
6P = 52 ← as required
A discrete randem variable is a variable that is randomly chosen and can only take on certain values.
A. True
B. False
Answer:
A. True.
Step-by-step explanation:
For example, the results of throwing a fair dice. The variable can only be 1,2,3,4,5,6.
Answer: True
A P E X
A discrete randem variable is a variable that is randomly chosen and can only take on certain values.
The set of possible values of n is {-2, 1; 4).
What is the set of possible values of m if
3m = n-7?
How do I solve it
Replace n in the equation with each given value and solve for m.
You are given n = {-2, 1, 4}
When n = -2:
3m = -2-7
3m = -9
m = -9/3
m = -3
When n = 1:
3m = 1-7
3m = -6
m = -6 /3
m=-2
When n = 4:
3m = 4-7
3m = -3
m = -3/3
m = -1
m = {-3, -2, -1}
PLEASE HELP ME!!! what are the roots of x in -10x^2+12x-9=0
Answer:
Option B.
Step-by-step explanation:
We have the following polynomial: -10x^2+12x-9=0
Multiplying by -1:
10x^2-12x+9=0
Using the quadratic formula, we find that the roots are:
0.6 ± 3√(6)/10i
Therefore, the correct answer is B.
(x-2)(-5x^2+x)=(x)(-5x^2)+(x)(x)+(-2)(-5x^2)+(-2)(x)
Answer:
Step-by-step explanation:
First we will solve the Left Hand Side:
(x-2)(-5x²+x)
Multiply the terms:
= -5x³+x²+10x²-2x
Solve the like terms
= -5x³+11x²-2x
Now we will solve the Right Hand Side:
(x)(-5x²)+(x)(x)+(-2)(-5x²)+(-2)(x)
Multiply the terms:
-5x³+x²+10x²-2x
Solve the like terms:
-5x³+11x²-2x
Hence it is proved that L.H.S = R.H.S....
Suppose Q and R are independent events. Find P(Q and R) if P(Q) = 7/15 and P(R) = 4/7
Answer:
4/15.
Step-by-step explanation:
In probability, there are two types of events: the ones that are not related to each other and the ones that are related to each other. The former types of events are called independent events. In such cases, since the occurrence of one event is not related to and does not affect the other event, therefore, the probabilities of both events can be multiplied if they occur together. It is given that:
P(Q) = 7/15.
P(R) = 4/7.
P(Q and R) = P(Q)*P(R) = 7/15 * 4/7 = 4/15.
Therefore, the probability is 4/15!!!
URGENT,PLEASE HELP ME !!!!!!!!!!!!!!!
Answer: The last one
Step-by-step explanation:
I think this because the graph starts from H the number of hours studied and when u add the numbers and divide them up which gives you the equation 65 + 50 . Any questions please text me. Have a nice day.
What is the probability of not drawing a red marble?
5/5
3/5
50%
30%
Answer:
50%
Step-by-step explanation:
There are 10 marbles total in the bag, and 5 of them are red. So, to find the probability of not drawing a red marble, you need to count how many marbles are not red.
There are 3 green marbles and 2 blue marbles so there are 5 marbles that are not red.
So you need to write this as a fraction so 5/10 of the marbles are not red.
None of the answer choices that are fractions match 5/10 or 1/2, so you need to convert 5/10 to a percent.
To convert it as a percent you divide 5 by 10, which is .50
Then you move the decimal point two places to the right so its 50%
So there is a 50% percent chance of not drawing a red marble.
What is the standard form for the quadratic function? g(x)=(x+1)^2−2
g(x)=x^2−2x−4
g(x)=x^2−1
g(x)=x^2+2x−1
g(x)=x^2−3
the standard form is g(x)=x^2+2x-1
Which of the following are remote interior angles of _1? Check all that apply.
Answer:
B and E
Step-by-step explanation:
The remote interior angles to ∠1 are the 2 opposite interior angles, that is
∠5 and ∠6
what is the gcf of 42 and 60
Answer:
The GCF of 42 and 60 is 6
Step-by-step explanation:
42: 1,2,3,6,7,14,21,42
60: 1,2,3,4,5,6,10,12,15,20,30,60
Answer:
6
Step-by-step explanation:
Factors of 42 = 1, 2, 3, 6, 7, 14, 21 and 42
Factors of 60 = 1 , 2 , 3 , 4 , 5 , 6 , 10 , 12 , 15 , 20 , 30 and 60
The highest factor which comes in both 42 and 60 is 6
Write ln2x+2lnx-ln3y as a single logarithm.
a. ln(2x/3y)
b. ln(3x/3y)
c. ln(2x^3/3y)
d. ln(x^3/3y)
Answer is C. ln(2x^3/3y) on Edge!
Answer:
Option C. [tex]ln(\frac{2x^{3}}{3y})[/tex]
Step-by-step explanation:
The given logarithmic expression is:
[tex]ln(2x)+2ln(x)-ln(3y)[/tex]
Using the power rule of logarithms: [tex]blog(a)=log(b)^{a}[/tex], the above expression can be written as:
[tex]ln(2x)+ln(x)^{2}-ln(3y)[/tex]
Using the product rule of logarithms: [tex]log(a)+log(b) =log(ab)[/tex], the above expression can be simplified further to:
[tex]ln(2x \times x^{2}) - ln(3y)\\\\=ln(2x^{3})- ln(3y)[/tex]
Using the quotient rule of logarithms: [tex]log(a)-log(b)=log(\frac{a}{b})[/tex], the above expression can be written as:
[tex]ln(\frac{2x^{3}}{3y})[/tex]
Hence option C gives the correct simplified answer.
(11z2+4z-6)+(4z-7+12z2)+(-8+13z2+4z)
Answer: [tex]36z^2+12z-21[/tex]
Step-by-step explanation:
You need to remember the multiplication of signs:
[tex](+)(+)=+\\(+)(-)=-\\(-)(-)=+[/tex]
In order to simplify the given the expression:
[tex](11z^2+4z-6)+(4z-7+12z^2)+(-8+13z^2+4z)[/tex]
You must distribute signs:
[tex]=11z^2+4z-6+4z-7+12z^2-8+13z^2+4z[/tex]
And finally, you must add the like terms:
[tex]=36z^2+12z-21[/tex]
Answer:
huifytyjctrxrtfygvjhk
Step-by-step explanation:
yeah he is right
There were 24 acts performing in
the talent show. Eight acts were
solo performances and the rest
were performed by a group. What
percent of the acts were group
performances?
F. 30%
G. 33 1/3 %
H. 60%
I. 66 2/3%
Find the total number of groups by subtracting the solo acts from the total acts:
24 - 8 = 16 group acts.
Now divide the number of group acts by the total number of acts:
16 /24 = =0.666
Multiply by 100:
0.666 x 100 = 66.6% = 66 2/3%
The answer is I.
Write an expression for the area of a square with side s = 2x + 5
Answer:
[tex]4x^2+20x+25[/tex] square units
Step-by-step explanation:
We are given that side of a square has the dimension [tex]s = 2x + 5[/tex] and using this, we are to write an expression for the area of this square.
We know that the formula of area of a square is given by:
Area of square = [tex]s^2[/tex]
So substituting the given value in the above formula to get:
Area of square = [tex](2x+5)^2 = (2x+5)(2x+5) = 2x(2x)+2x\times5+5(2x)+5\times5 = 4x^2+20x+25[/tex] square units
Answer:
[tex]A = 4x ^ 2 + 20x +25[/tex]
Step-by-step explanation:
Remember that all sides of a square have the same length. Therefore, the Area of a square is defined as:
[tex]A = s ^ 2[/tex]
Where s is the length of the sides of the squares.
In this case we know that the length of the sides is:
[tex]s = 2x + 5[/tex]
So the area is:
[tex]A = (2x +5) ^ 2[/tex]
We develop the expression and we have left that the area is:
[tex]A = 4x ^ 2 + 20x +25[/tex]
a. Find the length of the midsegment of an equilateral triangle with side lengths of 12.5 cm.
b. Given that UT is the perpendicular bisector of AB, where T is on AB, find the length of AT given AT = 3x + 6 and TB = 42 - x.
c. Given angle ABC has angle bisector BD, where AB = CB, find the value of x if AD = 5x + 10 and DC = 28 - x.
Answer:
a) The length of the mid-segment is 6.25 cm
b) The length of AT = 33 units
c) The value of x is 3
Step-by-step explanation:
a)
* Lets explain the mid-segment of a triangle
- A mid-segment of a triangle is a segment connecting the midpoints
of two sides of a triangle
- This segment has two special properties
# It is parallel to the third side
# The length of the mid-segment is half the length of the third side
∵ The triangle is equilateral triangle
∴ All sides are equal in length
∵ the side lengths = 12.5 cm
∵ The length of the mid-segment = 1/2 the length of the third side
∴ The length of the mid-segment = 1/2 × 12.5 = 6.25 cm
* The length of the mid-segment is 6.25 cm
b)
∵ UT is a perpendicular bisector of AB
∵ T lies on AB
∴ T is the mid-point of AB
∵ AT = BT
∵ AT = 3x + 6
∵ BT = 42 - x
- Equate AT and BT
∴ 3x + 6 = 42 - x
- Add x to both sides
∴ 4x + 6 = 42
- Subtract 6 from both sides
∴ 4x = 36
- Divide both sides by 4
∴ x = 9
∵ AT = 3x + 6
- Substitute x by 9
∴ AT = 3(9) + 6 = 27 + 6 = 33
* The length of AT = 33 units
c)
- In Δ ABC
∵ AB = BC
∴ Δ ABC is an isosceles triangle
∵ BD bisects angle ABC
- In the isosceles Δ the bisector of the vertex angle bisects the base
of the triangle which is opposite to the vertex angle
∵ AC is the opposite side of the vertex B
∴ BD bisects the side AC at D
∴ AD = CD
∵ AD = 5x + 10
∵ CD = 28 - x
∴ 5x + 10 = 28 - x
- Add x to both sides
∴ 6x + 10 = 28
- Subtract 10 from both sides
∴ 6x = 18
- Divide both sides by 6
∴ x = 3
* The value of x is 3
The true statements are:
a) The length of the midsegment is 6.25 cm
b) The length of AT = 33 units
c) The value of x is 3
The length of the midsegment
The length of the triangle is given as
L =12.5cm
So, the length of the midsegment is:
M = 0.5 * L
This gives
M = 0.5 * 12.5 cm
M = 6.25 cm
Hence, the length of the midsegment is 6.25 cm
The length of AT
The given parameters are:
AT = 3x + 6 and TB = 42 - x.
Since point T is the perpendicular bisector, then we have:
3x + 6 = 42 - x
Collect like terms
3x +x = -6 + 42
Evaluate
4x = 36
Divide both sides by 4
x = 19
Recall that:
AT = 3x + 6
So, we have:
At = 3 * 9 + 6
At = 33
Hence. the length of AT = 33 units
The value of x
We have:
AD = 5x + 10
DC = 28 - x
So, we have:
5x + 10 =28 - x
Collect like terms
5x + x = 28 -10
6x =18
Divide
x =3
Hence, the value of x is 3
Read more about lengths at:
https://brainly.com/question/19819849
Find the x value do that the line through the points (x,-9) and (0,1) has a slope of -4 PLEASE ANSWER
[tex]\bf (\stackrel{x_1}{x}~,~\stackrel{y_1}{-9})\qquad (\stackrel{x_2}{0}~,~\stackrel{y_2}{1}) \\\\\\ slope = m\implies \cfrac{\stackrel{rise}{ y_2- y_1}}{\stackrel{run}{ x_2- x_1}}\implies \cfrac{1-(-9)}{0-x}=\stackrel{\stackrel{slope}{\downarrow }}{-4}\implies \cfrac{1+9}{-x}=-4 \\\\\\ \cfrac{10}{-x}=-4\implies 10=4x\implies \cfrac{10}{4}=x\implies \cfrac{5}{2}=x[/tex]
Which of the following solids has a triangular cross section when the cross section is taken perpendicular to the base?
A.
square pyramid
B.
cube
C.
hexagonal prism
D.
rectangular prism
Answer:
A. square pyramid
Step-by-step explanation:
A square pyramid has a triangular cross section when the cross section is taken perpendicular to the base.
The solid that has a triangular cross section when the cross section is taken perpendicular to the base is a square pyramid. A cross section through the sloping triangular faces of the square pyramid will reveal a triangular shape.
To answer this, consider the properties of each option:
A square pyramid has a square base and triangular faces that meet at a common point above the base, resembling a series of tetrahedra joined together. When a cross section is taken perpendicular to its square base, it would indeed reveal a triangle shape as it would pass through these sloping triangular faces.
A cube would not result in a triangular cross section since it has all square faces.
A hexagonal prism has a hexagon as its base, and taking a cross section perpendicular to this base would yield a hexagon, not a triangle.
Similarly, a rectangular prism would result in a rectangle or square from such a cross section.
Therefore, the correct answer is a square pyramid.
Which of the following is best described as a pair of opposite angles formed
by intersecting lines?
O
A. Vertical angles
O
B. Supplementary angles
O
O
C. Complementary angles
D. Linear pair
Answer:
Vertical angles
Step-by-step explanation:
Vertical angles are the angles that happen opposite to each other in two intersecting lines. (These angles are congruent.)
Supplementary means that the two angles add up to be 180.
Complementary means the two angles add up to 90.
Linear pair are supplementary adjacent angles. (Adjacent means next to sharing the same vertex and a common ray.)
The given statement is the definition of vertical angles.
What are vertical angles?Vertical angles are either of two angles lying on opposite sides of two intersecting lines.
What are Supplementary angles?Supplementary angles are two angles whose sum is 180 degrees.
What are Complementary angles?Complementary angles are two angles whose sum is 90 degrees.
What are Linear pair?Linear pair of angles are formed when two lines intersect each other at a single point.
How to find which of the following is best described as a pair of opposite angles formed by intersecting lines?In the question, it is given to describe two angles as a pair of opposite angles formed by intersecting lines.According to the definition, these are vertical angles, which two angles lying on opposite sides of two intersecting lines.
Find more about "Vertical angles" here: https://brainly.com/question/14362353
#SPJ2
Patrick travels from A to B at an average speed of 8km/h and then he travels from B to C at an average speed of 6 km/h.It is given that Patrick travels 26.4 km in 234 minutes for the whole journey.Find the distance that Patrick travels from A to B.
Answer:
12 km
Step-by-step explanation:
So the situation is:
8 km/h for X hours
6 km/h for y hours
X * 8 + y * 6 = 26.4
and X + Y = 3.9 hours
Since 234/60 = 3.9 hours
You could write that X = 3.9 - Y
(3.9-Y) * 8 + y * 6 = 26.4
31.2 -8Y +6Y = 26.4
-2Y = -4.8
Y = 2.4 hours
X = 3.9-2.4 = 1.5 hours
So 1.5 * 8 = 12 km
Answer:
AB = 12km
Step-by-step explanation:
From the question we can get the following information,
The whole trip is 26.4 km and 3.9 hours ([tex]\frac{234}{60}[/tex]), and we can form the following two equations.
[tex]x + y = 3.9[/tex] and [tex](x*8km/h) + (y*6km/h) = 26.4km[/tex]
Where X is distance between A and B, and Y is distance between B and C. We can solve the first equation for X and plug X into the second equation.
[tex]x = 3.9 - y[/tex] ........ and we can plug it into the the second equation and solve for y
[tex]((3.9-y)*8)+(6y) = 26.4[/tex]
[tex](31.2-8y)+6y = 26.4[/tex]
[tex]31.2-2y = 26.4[/tex]
[tex]-2y = -4.8[/tex]
[tex]y = 2.4[/tex]
Now we can plug in y to the first equation to solve for x
[tex]x = 3.9-2.4[/tex]
[tex]x = 1.5[/tex]
Finally, we can multiplay 8km/h by 1.5 hours to find the distance from A to B
[tex]AB = 8km/h * 1.5h[/tex]
[tex]AB = 12km[/tex]
Let f(x) = -2x - 7 and g(x) = -4x + 6. Find (fxg)(-5).
Answer:
78
Step-by-step explanation:
Multiply f(x) and g(x) then evaluate for x = - 5
f(x) × g(x)
= (- 2x - 7)(- 4x + 6) ← substitute x = - 5 into the expression
= (10 - 7)(20 + 6)
= 3 × 26
= 78
For this case we have the following functions:
[tex]f (x) = - 2x-7\\g (x) = - 4x + 6[/tex]
We must find [tex](f * g) (x).[/tex] By definition we have to:
[tex](f * g) (x) = f (x) * g (x)[/tex]
So:
[tex](f * g) (x) = (- 2x-7) (- 4x + 6)[/tex]
We apply distributive property keeping in mind that:
[tex]- * - = +\\- * + = -\\(f * g) (x) = 8x ^ 2-12x + 28x-42\\(f * g) (x) = 8x ^ 2 + 16x-42[/tex]
We evaluate in [tex]x = -5[/tex]:
[tex](f * g) (- 5) = 8 (-5) ^ 2 + 16 (-5) -42\\(f * g) (- 5) = 8 * 25-80-42\\(f * g) (- 5) = 200-80-42\\(f * g) (- 5) = 78[/tex]
Answer:
[tex](f * g) (- 5) = 78[/tex]
Which exponential function is represented by the values in the table? A.f(x) = 1/2(4)x B.f(x) = 4(4)x C.f(x) = 4(1/2) D.f(x) = 1/2(1/2)^x
Answer:
The Answer is D
Step-by-step explanation:
If the Exponent is 1 or just x then it is linear.
If the Exponent is 2 or x^2 then it is quadratic* If the Exponent has and x, then this graph is exponential because anything to the power of X is exponential.
1/2(1/2)=0.25^x
Answer:
The Answer is C
Step-by-step explanation:
Just took ed2020 test
(3x-5)+(15-x)+(2x-3)
The perimeter is 35 ft.
Answer:
17x
Step-by-step explanation:
combine like terms,you would end up with 20x because if you combine 3x and 2x=5 then 5x+15x is 20x.then 20x-3 is 17x.
Help please!!!
What is the distance between the two endpoints in the graph below? If necessary, round your answer to two decimal places.
Answer:
A) 7.07
Step-by-step explanation:
[tex]The \: distance \: formula = \sqrt{(x_2 - x_1) ^{2} + (y_2 - y_1) ^{2} } [/tex]
[tex]P_1(-3, -2) \: \: \: \: \: \: \: \: \: \: \: P_2(2, 3)[/tex]
[tex]d = \sqrt{ {(2 - ( - 3))}^{2} + {(3 - ( - 2))}^{2} } \\ d = \sqrt{ {(2 + 3)}^{2} + {(3 + 2)}^{2} } \\ d = \sqrt{ {5}^{2} + {5}^{2} } \\ d = \sqrt{25 + 25} \\ d = \sqrt{25(1 + 1)} \\ d = \sqrt{25(2)} \\ d = \sqrt{25} \times \sqrt{2} \\ d = 5 \sqrt{2} \\d = 7.07106781187 \\ d = 7.07[/tex]
Answer: A. 7.07 units
Step-by-step explanation:
The distance between any two points (a,b) and (c,d) is given by :-
[tex]D=\sqrt{(d-b)^2+(c-a)^2}[/tex]
From the given picture , we can see that the line is passing through (2,3) and (-3,-2).
The distance between (2,3) and (-3,-2) is given by :-
[tex]D=\sqrt{(-2-3)^2+(-3-2)^2}\\\\\Rightarrow\ D=\sqrt{(-5)^2+(-5)^2}\\\\\Rightarrow\ D=\sqrt{25+25}=\sqrt{50}\\\\\Rightarrow\ D=7.07106781187\approx7.07[/tex]
Hence, the distance between the two endpoints = 7.07 units
(X+3)(x^2-6x+5). Please help multiply polynomials
Answer:
s is neding some more in fo
Step-by-step explanation:
Answer:
x³ - 3x² - 13x + 15
Step-by-step explanation:
Each term in the second factor is multiplied by each term in the first factor, that is
x(x² - 6x + 5) + 3(x² - 6x + 5) ← distribute both parenthesis
= x³ - 6x² + 5x + 3x² - 18x + 15 ← collect like terms
= x³ - 3x² - 13x + 15
Five men can install 200 yards of pipeline in an eight hour day three men are added to the job assuming the individuals rates remain the same how many days will it take the entire crew to install 2240 yards of pipeline
Answer:
7 days
Step-by-step explanation:
Five men do 200 yards in one day
One man does 200/5 = 40 yards in 1 day.
=============
Now you want to know something about 8 men
8 men can do 40 * 8 = 320 yards in 1 day
=============
2240 yards / 320 yards = 7 days
What polynomial has roots of −6, 1, and 4?
x3 − 9x2 − 22x + 24
x3 − x2 − 26x − 24
x3 + x2 − 26x + 24
x3 + 9x2 + 14x − 24
Answer:
The correct option is C
Step-by-step explanation:
We have given the roots -6, 1 and 4.
Write down the roots:
x= -6 , x=1 , x=4
Rewrite the roots as an expression:
x+6=0
x-1=0
x-4=0
Now we have the following expressions:
=(x+6)(x-1)(x-4)
Now Multiply the terms:
=(x²-x+6x-6)(x-4)
=(x²+5x-6)(x-4)
=x(x²+5x-6) -4(x²+5x-6)
=x³+5x²-6x-4x²-20x+24
Solve the like terms:
=x³+x²-26x+24
Thus the correct option is C....
Answer:
aaaaaaaa top one wrong
Step-by-step explanation:
What is the value of in the equation 5x+3=4x
Answer:
- 3
Step-by-step explanation -
- 5x from both sides -> 3 = -1x .
then divide each side by - 1 -> -3 = x
Answer:
-3
Step-by-step explanation:
5x+3=4x
Subtract 5x on both sides.
5x+3-5x=4x-5x
Simplify.
3=-1x
3=-x
Take opposite of both sides.
-3=x
x=-3
Dru is constructing a bridge. It takes 12 cubic yards of concrete to make a bridge that is
4 inches thick.
20. Write a direct variation equation that relates c and t, where c is cubic yards of concrete and t
is thickness in inches.
also, How many cubic yards of concrete does Dru need to make the bridge 6 inches thick?
Answer:
c=3t is the equation
18 cubic yards of concrete is what we need for a 6 inch thick bridge.
Step-by-step explanation:
If something directly varies, that means there is a constant, k, such that when you multiply it to one variable you always get the other variable.
That is for this particular problem we have c=kt where c is cubic yards and t is thickness in inches.
So we are given from the first sentence: 12 cubic yards and 4 inches thick which means we have:
12=k(4)
Divide both sides by 4:
12/4=k
Simplify:
3=k
So the equation is c=3t for any point (c,t) in this relation.
So we want to know many cubic yards of concrete (we want to know (c) so that Dru can build a 6 inch (t) thick bridge.
c=3(6)
c=18
18 cubic yards
Complete: 45° C = ___° F
A. 81 B. 77 C. 25 D. 13
Answer:
113ºF
Step-by-step explanation:
Remember that exist a conversion rule that states:
[tex]F=\frac{9*C}{5} +32[/tex]
using it we have the following expression:
[tex]1.8*(45)+32=113[/tex]
a ladder is 40 ft and an 80 degree decline its an isosceles right triangle what so my sides equal
Answer:
The sides are equal to
x=6.9 ft and y=39.4 ft
Step-by-step explanation:
step 1
Find the adjacent side to the angle of 80 degrees
Let
x ----> the adjacent side to the angle of 80 degrees
we know that
The function cosine of angle of 80 degrees is equal to divide the adjacent side to the angle of 80 degrees by the hypotenuse (40 ft)
cos(80°)=x/40
x=(40)cos(80°)
x=6.9 ft
step 2
Find the opposite side to the angle of 80 degrees
Let
y ----> the opposite side to the angle of 80 degrees
we know that
The function sine of angle of 80 degrees is equal to divide the opposite side to the angle of 80 degrees by the hypotenuse (40 ft)
sin(80°)=y/40
y=(40)sin(80°)
y=39.4 ft